2020
DOI: 10.3389/fmed.2020.00177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Label Noise on Deep Learning-Based Skin Cancer Classification

Abstract: Recent studies have shown that deep learning is capable of classifying dermatoscopic images at least as well as dermatologists. However, many studies in skin cancer classification utilize non-biopsy-verified training images. This imperfect ground truth introduces a systematic error, but the effects on classifier performance are currently unknown. Here, we systematically examine the effects of label noise by training and evaluating convolutional neural networks (CNN) with 804 images of melanoma and nevi labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The image analysis was performed by the respective physicians in all reports. Several landmark studies have recently shown that AI performed on par with dermatologists in the distinction of nevi from melanoma based on dermoscopic images [ 43 , 44 , 45 ]. Similarly, future studies are warranted to investigate whether the analysis of 3-D TBP images using AI is also feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The image analysis was performed by the respective physicians in all reports. Several landmark studies have recently shown that AI performed on par with dermatologists in the distinction of nevi from melanoma based on dermoscopic images [ 43 , 44 , 45 ]. Similarly, future studies are warranted to investigate whether the analysis of 3-D TBP images using AI is also feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several other barriers exist with regards to the implementation of AI in clinical dermatology, which have been extensively discussed by Gomolin et al as well, including generalizability, standardization, and interpretability (3,(64)(65)(66)(67). To summarize, several AI algorithms are trained using input data from limited populations, thus they may not be effective in patients from different settings or with unique phototypes.…”
Section: Editorial On the Research Topic The Emerging Role Of Artificial Intelligence In Dermatologymentioning
confidence: 99%
“…The shifts between two datasets represent that the pattern-recognition abilities acquired from large datasets may not apply well to our medical task. Second is the noisy label problem [ 16 ]. Inevitably, there are always some cancerous lesions that come from high-grade patients but do not exhibit characteristics sufficient to discriminate them from low-grade patients, resulting in the mismatch between the manual labels and the actual labels.…”
Section: Introductionmentioning
confidence: 99%